Per insegnare la filosofia on-line: suggestioni platoniche e questioni didattiche - Angela Arsena (LED Edizioni Universitarie, 2017)
On teaching philosophy on-line: platonic suggestions and pedagogical issues. The debate about the problems inherent the usage of the tools employed for an effective transmission of the philosophical message are extremely ancient. Plato's hesitation when faced with the technique of written text, together with the solutions and the pedagogical strategies found by the Greek philosopher, represent an authoritative model that may become a contemporary paradigm for solving the problem of the construction of logical connectives that determine a new phenomenology of philosophical concepts transmitted through the Internet. In fact, the cultural revolution triggered by the diffusion of writing in the classic period in Greece shows that pedagogy, and teaching techniques, are not independent from the media, in the sense that the choice of the media participates in the construction, and in the deconstruction, of knowledge, by influencing and modifying it. The logical connectives underlying an alphabetic-grammatical cultural transmission are found as more stable, linear and monolithic than the more fluid logical connectives underlying an oral cultural transmission, based on the reiteration of memory. Inevitably, a transmission of knowledge relaying on the net operates a deconstruction of the logical connectives. This evidence cannot be neglected while building the logic and conceptual framework of a technique for teaching philosophy on-line.